99mTc-HDP SPECT-CT Aids Localization of Joint Injections in Degenerative Joint Disease of the Foot and Ankle. (August 2015) - Parthipun, Arum; Moser, Joanna; Mok, Wing; Paramithas, Anton; Hamilton, Paul; Sott, Andrea Helene
Background: Pain relating to degenerative joint disease within the foot and ankle can be difficult to localize with clinical examination alone due to the complex anatomy of the joints. The aim of this study was to determine whether single-photon emission computed tomography combined with conventional computed tomography (SPECT-CT) could be used to localize the site of degenerative joint disease for intra-articular injection and thereby improve the clinical success of the procedure. Methods: A prospective study was performed involving 203 patients who had undergone triple-phase 99m Tc-hydroxymethylene diphosphonate bone scans with SPECT-CT of the foot and ankle for degenerative joint disease. Fifty-two patients went on to have joint injections for degenerative joint disease, with clinical follow-up. Correlation with the clinical diagnosis and the outcome of intra-articular injections with 0.5% bupivacaine and 80 mg of Depo-Medrone was performed. A successful outcome was determined by an improvement in the visual analog pain score of at least 50%. Results: In 19 (37%) patients, the site of degenerative joint disease determined by SPECT-CT differed from the initial clinical assessment and resulted in a change in management. Overall, 46 (88%) patients showed an improvement in symptoms. Conclusion: The study demonstrated a high clinical success rate for SPECT-CT-guided joint injections. The technique was useful in localizing degenerative joint disease of the ankle, hindfoot, and midfoot as an adjunct to clinical examination. Level of Evidence: Level IV, case series.